Seeking Champions for Change: A Positive Deviance Approach for Social Work. Issue 2 (April 2019) - Wolfer, Terry A.; Wilson, Betty L.
Given growing interest in and need for social innovation, social workers will benefit from knowing about positive deviance (PD), an approach that capitalizes on local creativity and strengths. The PD approach seeks community (or organizational) members who have developed solutions for problems with which other members struggle, despite their having similar resources and constraints. Rather than rely on professional expertise and skills to solve intractable problems in communities, the PD approach evokes a "new way of thinking" that promotes indigenous leadership and community responsibility for problems and solutions. This article outlines key components of the PD approach, describes steps for implementing PD, and discusses implications for social work.